2018
DOI: 10.1111/ijn.12643
|View full text |Cite
|
Sign up to set email alerts
|

Caring for a patient with delirium in an acute hospital: The lived experience of cardiology, elderly care, renal, and respiratory nurses

Abstract: The need for education across specialities, with a combination of classroom and simulation teaching. Alongside, the development of structures to support the development of nursing teamwork and reporting of near miss incidents that occur with patients during an episode of delirium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 42 publications
0
24
0
Order By: Relevance
“…Participants in the study reported high levels of fear, using terms such as 'terrifying' and 'scared', emotions that are associated with aggressive behaviour (Brooke & Manneh 2018) Reduced sense of personal autonomy has also been associated with the aggressive behaviours sometimes observed in people with delirium (Darbyshire et al 2016;Fagerberg & J€ onhagen 2002). Understanding these emotions provides nurses with opportunities for intervention, including building trust, reorientation, and promoting a safe environment with predictable stimuli.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants in the study reported high levels of fear, using terms such as 'terrifying' and 'scared', emotions that are associated with aggressive behaviour (Brooke & Manneh 2018) Reduced sense of personal autonomy has also been associated with the aggressive behaviours sometimes observed in people with delirium (Darbyshire et al 2016;Fagerberg & J€ onhagen 2002). Understanding these emotions provides nurses with opportunities for intervention, including building trust, reorientation, and promoting a safe environment with predictable stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…Participants in the study reported high levels of fear, using terms such as ‘terrifying’ and ‘scared’, emotions that are associated with aggressive behaviour (Brooke & Manneh ) Reduced sense of personal autonomy has also been associated with the aggressive behaviours sometimes observed in people with delirium (Darbyshire et al . ; Fagerberg & Jönhagen ).…”
Section: Discussionmentioning
confidence: 99%
“…Experiencing delirium and having flashbacks of delirious episodes is frightening for patients and affects their psychological and emotional well-being [11][12][13]. Providing appropriate care to delirious patients imposes a great burden on healthcare professionals, for example, because of difficult behaviors of patients and overlapping symptoms with dementia [14,15].…”
Section: Deliriummentioning
confidence: 99%
“…Low detection rates of delirium are often related to low delirium awareness, inadequate knowledge and education, lack of time, feeling uncomfortable with delirium assessment, and missing co-operation between professions. However, if the presence of delirium and/or increased risks are detected, such barrierstogether with negative attitudes towards deliriumare also related to suboptimal delirium management [2,14,[17][18][19].…”
Section: Deliriummentioning
confidence: 99%
See 1 more Smart Citation